Korupsi, Transisi Demokrasi & Peran Organisasi Civil Society (CSO): Sebuah Tinjauan Teoritis - BUDI SETIYONO, BUDI SETIYONO (Program Magister Ilmu Politik, Universitas Diponegoro, 2010)
Abstract Corruption is a problem in countries around the world. Nevertheless, corruption exists in these countries in many different ways including causes, forms, degrees and consequences. Subsequently, an effective effort to curb corruption needs to accommodate multiple socio-political contexts that may be factors in the problem of corruption, especially in transitional democracies where the situation is typically more complex. Studies on corruption in transitional democracies —and more broadly in the developing world— have increased since the last two decades following the end of the Cold War. This increased attention is partly driven by awareness among experts across disciplines that corruption potentially hampers economic development, reduces the quality of public services, and distorts democratic values in general. In most developing countries, corruption undermines and jeopardises the democratic transition processes that are taking place. Recent studies generally have recognised the importance of understanding the social context of corruption and try explicitly to pinpoint the social situations that make corruption more likely to occur in transitional democracies. As well, such studies offered recommendations that suited specific social dynamics of the countries. Many of the studies generally consider that CSOs carry out a significant —if not central— position in the struggle against corruption; for two reasons: (1) Civil society leaders have become leading actors in terminating authoritarian regime, so they could continue their role in consolidating democracy, including combatting corruption; and (2) CSOs need to step forward in fighting corruption because of the failure of the state in dealing with the problem. Keywords: corruption, democracy, civil society